2005
DOI: 10.1038/sj.pcan.4500785
|View full text |Cite
|
Sign up to set email alerts
|

Association between hormonal genetic polymorphisms and early-onset prostate cancer

Abstract: We investigated the association between seven polymorphisms in four candidate genes involved in vitamin D and androgen metabolism with early-onset prostate cancer (CaP) risk. The polymorphisms were genotyped in 288 UK males who were diagnosed with CaP at the age of 55 y or younger and up to 700 population-based controls. An additional 50 cases (not selected for age) and 76 controls were also genotyped. Short (p22 repeats) AR (CAG) n repeats were associated with a significantly reduced risk of early onset CaP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…[27][28][29][30] In our study, we confirm a lack of association between V89L and risk of prostate cancer. The metaanalysis could not exclude the possibility of an association between the A49T polymorphism and risk of prostate cancer, as confirmed in our study.…”
Section: Discussionsupporting
confidence: 74%
“…[27][28][29][30] In our study, we confirm a lack of association between V89L and risk of prostate cancer. The metaanalysis could not exclude the possibility of an association between the A49T polymorphism and risk of prostate cancer, as confirmed in our study.…”
Section: Discussionsupporting
confidence: 74%
“…Scariano et al (20) genotyped 33 males with early onset prostate cancer and found that the expression of at least one SRD5A L allele in young males with prostate cancer was associated with a more significant disease at the time of presentation as was defined by the pretreatment PSA level, clinical staging and Gleason score when compared with affected subjects harboring the more common SRD5A2 V variant. Similar results were published by other studies (34,42). Cicek et al (34) confirmed the association between the SRD5A2 polymorphism and increased risk of prostate cancer in males diagnosed at an earlier age or with more aggressive disease (OR, 2.35; 95% CI, 1.41-3.92; P=0.001 and OR, 1.63; 95% CI, 0.98-2.72; P=0.06, respectively).…”
Section: No Of Cases (%) -------------------------------------------supporting
confidence: 80%
“…The differences in androgen levels may be due to variation in activity or expression of the enzymes responsible for metabolism of androgens. Most epidemiologic studies have focused on enzymes involved in production of androgens, such as CYP3A4 (10)(11)(12)(13), CYP17 (14)(15)(16)(17)(18)(19)(20)(21)(22), CYP3A43 (23), and SRD5A2 (22,24). Although differences in androgen levels may reflect variation in catabolism, fewer studies (25)(26)(27)(28) have evaluated this hypothesis.…”
Section: Introductionmentioning
confidence: 99%